St. Vincent and the Grenadines : 2002 Article IV Consultation -Staff Report; and Public Information Notice on the Executive Board Discussion. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
This 2002 Article IV Consultation highlights that real GDP for St. Vincent and the Grenadines grew by a modest u percent in 2001, well below the 4 percent average for the previous three years. Preliminary estimates for 2002 indicate about a pickup in real GDP growth to about 1 percent owing to a strong rebound in agriculture prior to tropical storm Lili in late September, and construction activity as public sector projects were implemented. Inflation was about 1 percent in 2001 and 2002, and unemployment is reported to remain high.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet